A Socio-Technical User Based Perspective for Urban Transport Solutions - The Fjordbus Case: Udvidet resumé - Luengas, Camilo Andrés Perdomo (Proceedings from the Annual Transport Conference at Aalborg University, 2021)
In Aalborg, Denmark the Center for Logistik og Samarbejde (CLS) and several organisations have been working since 2019 on the design of an autonomous passenger ferry (Fjordbus). The Fjordbus will initially sail between Musikens Hus and the new urban area in Stigsborg. The primary purpose of the Fjordbus is to become a transport solution to connect the population of Aalborg and Nørresundby. The Fjordbus will transport around 25 people and it will carry onboard objects such as baby carriages, bicycles, and wheelchairs.